STUDENTS’ CHARACTER AND PORTRAIT IN ENGLISH LITERATURE - Abdullayeva Nabiya Idrisovna (International Engineering Journal For Research & Development, 2020)
The article depicts the student's character in English literature. The role, genesis, national nature, poetic-typological features and the portrait of students in the works of English literary writers , their character’s features, similarities and differences. The article presents samples from English literature, analyzes and studies comparatively and typologically. The comparative study of the works of world figures analyzed in the article will have a positive impact on the development of our international literature and will promote the reading literary books and reading culture.